2021
DOI: 10.1615/intjmedmushrooms.2021038277
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Medicinal Mushrooms in Brain Cancer Therapies: Review

Abstract: Medicinal mushrooms are considered an unlimited source of polysaccharides (mainly β-glucans) and polysaccharide-protein complexes and possess various immunological and anticancer properties. In addition, their use in integrative medicine leads to a clear reduction of side effects in patients undergoing chemotherapy or radiotherapy. The literature reports a number of beneficial effects of using mushrooms as health supplements in patients affected by highgrade glioma. The effects of medicinal mushrooms on side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Schizophyllum commune, which accounted for 5.26% of the total isolated strains in this study, was recently found to cause mycotic disease in people on a rare basis, especially via cutaneous infection [ 62 ]. Although this fungal species is not commonly considered as pathogenic to humans, being mostly regarded as a medicinal mushroom [ 63 ], S. commune was indicated as a possible cause of pulmonary basidiomycosis by Unno et al [ 64 ], while inhalation of S. commune spores has been recently linked to allergic bronchopulmonary mycosis (ABPM) or allergy-related bronchopulmonary infections and sinusitis [ 65 , 66 ]. Furthermore, S. commune infection cases have increased significantly in the last few decades, since the first case of onychomycosis described by Kligman in 1950 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schizophyllum commune, which accounted for 5.26% of the total isolated strains in this study, was recently found to cause mycotic disease in people on a rare basis, especially via cutaneous infection [ 62 ]. Although this fungal species is not commonly considered as pathogenic to humans, being mostly regarded as a medicinal mushroom [ 63 ], S. commune was indicated as a possible cause of pulmonary basidiomycosis by Unno et al [ 64 ], while inhalation of S. commune spores has been recently linked to allergic bronchopulmonary mycosis (ABPM) or allergy-related bronchopulmonary infections and sinusitis [ 65 , 66 ]. Furthermore, S. commune infection cases have increased significantly in the last few decades, since the first case of onychomycosis described by Kligman in 1950 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: 1 nerve growth factor (NGF), 2 inducible nitric oxide synthase (iNOS), 3 mitogen-activated protein kinase (MAPK), 4 homologous protein (CHOP), 5 insulin-degrading enzyme (IDE), 6 Alzheimer's disease (AD), 7 8-hydroxy-2'-deoxyguanosine (8-OHdG), 8 thiobarbituric acid reactive (TBARS), 9 proliferating cell nuclear antigen (PCNA), 10 doublecortin (DCX), 11 interleukin 6 (IL-6), 12 cyclooxygenase-2 (COX-2), 13 superoxide dismutase 1 (SOD-1), 14 nuclear factor erythroid 2-related factor 2 (Nrf2), 15 N-methyl-D-aspartate receptor 1 (NMDAR1), 16 metabotropic glutamate receptor 2 (mGlutR2), 17 transforming growth factor beta 1 (TGF-beta1).…”
Section: Ergothioneine-enriched Primordiummentioning
confidence: 99%
“…IBD 15 Reducing the 5-Fu-induced GM dysbiosis, suppressing tumor growth, and inhibiting inflammatory markers. [120] Abbreviations: 1 H. erinaceus polysaccharides (HEPs), 2 shorty-chain fatty acid (SCFA), 3 H. erinaceus LGAM 4514 in 100% beech sawdust (HEBS), 4 H. erinaceus LGAM 4514 in olive pruning residues (HEOLRP), 5 gut microbiota (GM), 6 alkaline phosphatase (ALP), 7 low-density lipoprotein (LDL), 8 uric acid (UA), 9 creatinine (CREA), 10 body weight (Bw), 11 ulcerative colitis (UC), 12 purified unique polysaccharide isolated from H. erinaceus mycelium (EP-1), 13 dextran sulfate sodium (DSS), 14 low-weight polysaccharide from H. erinaceus with Mw: 9.9 kDa (HEP10), 15 intestinal bowel disease (IBD), 16 cyclophosphamide (CTX), 17 tight junctions (TJ), 18 mucin (MUC).…”
Section: Akkermansia Muciniphila Proteobacteriamentioning
confidence: 99%
See 1 more Smart Citation